Erratum to: Author’s Reply to Brocherie and Millet: ‘Is the Wet-Bulb Globe Temperature (WGBT) Index Relevant for Exercise in the Heat?’ (Sports Medicine, (2015), 10.1007/s40279-015-0392-x) - P‚riard J.D. (Springer International Publishing, 2020)
10.1007/s40279-015-0414-8